STUDY OF THE INFLUENCE OF THE PRESSURE AT THE INLET TO THE COMPLEX GAS TREATMENT UNIT ON THE RESERVOIR PRESSURE AND GAS RECOVERY FACTOR OF THE FIELD - Kondrat R. М.; Dremliukh, N. S.; Matiishyn, L. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2024)
The reasons for the production of residual hydrocarbons and the main directions for increasing the final gas recovery factor of fields under gas conditions are characterized. A methodology for studying the influence of the pressure at the inlet to the complex gas treatment unit on the value of reservoir pressure and the gas recovery factor of a field is presented. For the conditions of a model well, the influence of the pressure at the inlet to the complex gas treatment unit on the reservoir pressure, the gas recovery factor of the field, and the parameters of well operation and gas collection system operation was studied using mathematical dependencies. The research results are presented in the form of graphical dependencies of the gas recovery factor on the value of the pressure at the inlet to the gas treatment unit and the gas recovery factor on the degree of pressure reduction at the inlet to the gas treatment unit. According to the research results, the gas recovery factor decreases with increasing pressure at the inlet to the CCGTU. The results of the studies performed on the example of a model well indicate a high technological efficiency of the effect of reducing the pressure at the inlet to the gas treatment unit on the degree of gas recovery from the field.